On Biology and Technology: The Economics of Managing Biotechnologies - Timo Goeschl; Timothy Swanson (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper considers those sectors of the economy that operate under the same regimes of rewarding private innovators as others, but differ in that they face recurring problems of resistance, as occur in the pharmaceutical and agricultural industries. This recurrence originates in the natural processes of selection and evolution among humanity's biological competitors. The paper examines the capacity for decentralised patent-based incentive mechanisms to result in socially optimal outcomes in these sectors under scale- and speed-dependent evolution of pathogens. It demonstrates that there is a fundamental incompatibility between the dynamics of the patent system and the dynamics of the resistance problem under both types of evolution. Under scale-dependent evolution, the externalities within a patent-based system indicate that decentralised mechanisms will result in systematic underinvestment in R&D that decreases further with an increasing severity of the resistance problem. Under speed-dependent evolution, a patent-based system will fail to target socially optimal innovation size. The overall conclusion is that patent-based incentive mechanisms are incapable of sustaining society against a background of increasing resistance problems. The paper concludes with appropriate policy implications of these results.
Keywords: Q16; 330; Biotechnology; R&D; Patents; Biotechnologie-Industrie; Patent; Industrieforschung; Allokation; Industrieforschung; Innovation; Theorie